2007
DOI: 10.1038/sj.ejcn.1602610
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber intake, dietary glycemic index and load, and body mass index: a cross-sectional study of 3931 Japanese women aged 18–20 years

Abstract: Objective: Few observational studies have investigated dietary fiber intake and dietary glycemic index (GI) and glycemic load (GL) simultaneously in relation to obesity, particularly in non-Western populations. We examined the associations between dietary fiber intake and dietary GI and GL, and body mass index (BMI) in young Japanese women. Design: Cross-sectional study. Subjects: A total of 3931 female Japanese dietetic students aged 18-20 years from 53 institutions in Japan. Methods: Dietary fiber intake and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
50
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 46 publications
6
50
1
1
Order By: Relevance
“…Fibre may contribute to prevent weight gain, and consequently to reduce the risk of atherosclerosis. In fact, some studies assessing BMI instead of IMT as the main outcome have found inverse relationships, as we did between BMI and DF intake (Ludwig et al, 1999;Liu et al, 2003;Lairon et al, 2005;Bes-Rastrollo et al, 2006;Murakami et al, 2007). However, others did not find this association (Pietinen et al, 1996;Wu et al, 2003).…”
Section: Discussionmentioning
confidence: 45%
“…Fibre may contribute to prevent weight gain, and consequently to reduce the risk of atherosclerosis. In fact, some studies assessing BMI instead of IMT as the main outcome have found inverse relationships, as we did between BMI and DF intake (Ludwig et al, 1999;Liu et al, 2003;Lairon et al, 2005;Bes-Rastrollo et al, 2006;Murakami et al, 2007). However, others did not find this association (Pietinen et al, 1996;Wu et al, 2003).…”
Section: Discussionmentioning
confidence: 45%
“…Actually, there was positive association of dietary GI and GL with BMI in the same data set of young Japanese women. 28 Additionally, we previously reported a significant positive association between dietary GI and BMI (P for trend ¼ 0.001) among Japanese women aged 20-78 years. 26 Lin et al 29 also found a positive relation between rice dietary pattern and waist circumference and BMI among Hispanic elders.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, legume and cereal components such as soluble fiber, low-GI carbohydrates, proteins and other bioactive substances can potentially improve weight loss by means of favourable effects on energy regulation (26). In fact, there are several studies indicating that increased legume consumption is inversely related with the body mass index (27,28).…”
Section: Discussionmentioning
confidence: 99%